Computational Simulation of the Thermal Performance of a Solar Air Heater Integrated with a Phase Change Material - Reyes-Salinas, A; Bubnovich, V; Diaz-Diaz, M (American Society of Mechanical Engineers, 2019)
The performance of a solar collector with wax as a phase change material (PCM) located in a set of staggered pipes configuration was simulated computationally in this work. For the solar radiation of Chile, the accumulation of heat in the PCM system and the heat release at different time intervals were analyzed during the process of energy capture in summer: (a) without wax and with airflow, (b) with wax and without airflow, and (c) with wax and with airflow. Furthermore, the effects of solar radiation (summer and winter) airflow in the collector were analyzed on the performance of the system. The simulation results show that the use of a PCM in a solar air heater allows to store greater amounts of energy and it helps to extend the period of time when the air coming out of the collector has an elevated temperature. By increasing the airflow rate, the efficiency of the system increases and also the energy released to the air to be absorbed. © 2019 by ASME.